2020
DOI: 10.1212/cpj.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte reconstitution after DMF discontinuation in clinical trial and real-world patients with MS

Abstract: BackgroundDelayed-release dimethyl fumarate (DMF) has demonstrated robust efficacy in treating patients with relapsing-remitting multiple sclerosis. Decreases in absolute lymphocyte count (ALC) are a well-known pharmacodynamic effect of DMF treatment, but lymphocyte recovery dynamics are not well characterized after discontinuation of DMF.MethodsData sources included the Biogen DMF integrated clinical trial data set, a retrospective US chart abstraction study, and data from MSBase. We assessed rate and time co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Patients with severe prolonged lymphopenia (i.e., severe lymphopenia that lasted for ⩾6 months) were analyzed separately ( N = 38) as this cohort is not considered representative of current DMF use based on current ALC monitoring recommendations; these data have been previously presented. 7…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with severe prolonged lymphopenia (i.e., severe lymphopenia that lasted for ⩾6 months) were analyzed separately ( N = 38) as this cohort is not considered representative of current DMF use based on current ALC monitoring recommendations; these data have been previously presented. 7…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been demonstrated that reconstitution rate is dependent upon duration of lymphopenia, specifically if lymphopenia persists >6 months, the estimated rate of reconstitution is significantly slower compared with patients with less persistent lymphopenia. 7…”
Section: Methodsmentioning
confidence: 99%
“…Clinical trial and real-world data demonstrate that also grade III lymphopenia is usually reversible, with the duration of lymphopenia before treatment cessation as a major determinant of the interval to ALC recovery. 3 In patients with severe, prolonged lymphopenia for ⩾3 years, lymphocyte reconstitution was longer (12-18 months) than in patients with lymphopenia persisting for < 6months (2-3 months). In the reported patient, grade III lymphopenia was detected at 6 months after treatment start and treatment was stopped after 12 months according to current guidelines.…”
mentioning
confidence: 92%
“…In the clinical study program, no association of lymphocyte recovery and early drops of ALC within the first 6 months on treatment were observed. 3 Yet, higher incidence of prolonged and severe lymphopenia in patients with early ALC decrease argues for frequent laboratory testing; the European label was recently updated to recommend enhanced vigilance in patients with lymphopenia. 4 This is of importance considering recent population-based data on incomplete adherence to laboratory testing with potential sex differences.…”
mentioning
confidence: 99%
“…6 Interestingly, duration of therapy once grade III lymphopenia has developed is an important factor in lymphocyte reconstitution rate 6,9 A study revealed that the majority of patients who discontinued DMF within 6 months of grade III lymphopenia onset demonstrated lymphocyte reconstitution above the lower limit of normal (⩾0.91 × 10 9 /L) within 2-4 months following therapy discontinuation whereas patients who remained on DMF for 3 years after grade III lymphopenia onset required 12-18 months on average for lymphocyte reconstitution after DMF cessation. 9 The importance and implications of lymphopenia in the setting of DMF therapy may not be fully appreciated, but a persistent low ALC is a risk factor for acquiring opportunistic infections, including progressive multifocal leukoencephalopathy (PML). 5 Here, we present a patient who developed grade III lymphopenia within 6 months of DMF initiation, and despite treatment cessation 6 months later.…”
Section: Introductionmentioning
confidence: 99%